Analysis of modulation parameters of high frequency digital modulation signal - Anuar, Hardy Azmir (2004)
High Frequency (HF) radio communication has grown both in the business and private sectors such as for voice, data communication and remote computer accessing from merely sending Morse code. It is still widely used all over the world along with satellite communication. Spectrum surveillance and monitoring is useful in confirmation to the HF frequency allocation because of it scarce resource shared by many users and as part of the radio surveillance it is important to monitor data communication over the air space. The estimation of modulation parameters allows the signal to be classified and to recover the binary information from the signal. This paper reports the study of time-frequency transform applied to HF data signals and the estimation of the signal parameters. The method described is the Short Time Frequency Transform (STFT) also known as the spectrogram develops from standard Fourier Transform techniques to handle non-stationary data. This method is the most basic of time-frequency distributions. The signal under test is a simulated signal either with or without the present of random white noise signal. The result shows an approximation of the frequency, type of modulation and bit rate presence within the signal under test